Impediments and constraints in the uptake of water sensitive urban design measures in greenfield and infill developments - Sharma, A.; Cook, Simon; Tjandraatmadja, G.; Gregory, A. (I W A Publishing, 2012)
Water sensitive urban developments are designed with integrated urban water management concepts and water sensitive urban design measures. The initiatives that may be included are the substitution of imported drinking water with alternative sources using a fit-for-purpose approach and structural and non-structural measures for the source control of stormwater. A water sensitive approach to urban development can help in achieving sustainability objectives by minimising disturbance to ecological and hydrological processes, and also relieve stress on conventional water systems. Water sensitive urban developments remain novel in comparison with conventional approaches, so the understanding and knowledge of the systems in regards to their planning; design; implementation; operation and maintenance; health impacts and environmental impacts is still developing and thus the mainstream uptake of these approaches faces many challenges. A study has been conducted to understand these challenges through a detailed literature review, investigating a large number of local greenfield and infill developments, and conducting extensive consultation with water professionals. This research has identified the social, economic, political, institutional and technological challenges faced in implementing water sensitive urban design in greenfield and infill developments. The research found in particular that there is the need for long-term monitoring studies of water sensitive urban developments. This monitoring is important to validate the performance of novel approaches implemented and improve associated guidelines, standards, and regulatory and governance frameworks, which can lead to mainstream acceptance of water sensitive urban development approaches. The dissemination of this research will help generate awareness among water professionals, water utilities, developers, planners and regulators of the research challenges to be addressed in order to achieve more mainstream acceptance of water sensitive approaches to urban development. This study is based on existing water sensitive urban developments in Australia, however, the methodology adopted in investigating impediments to the uptake of these developments can be applied globally. It is hoped that insights from this study will benefit water professionals in other countries where there is also a move towards water sensitive urban development. © CSIRO 2012.